DEVELOPMENT AND VALIDATION OF HIGH-PERFORMANCE THIN LAYERCHROMATOGRAPHIC METHOD FOR CIPROFLOXACIN BY QUALITY BY DESIGN APPROACH - V TATHE, SHRADDHA; P MAHAJAN, MORESHWAR; G PINJARKAR, RASHMI; M KASHID, ARUN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The aim of this paper is to create a new, systematic high-performance thin-layer chromatography (HPTLC) method for ciprofloxacin that is based on quality by design (QbD). Methods: The mobile phase was chloroform: IPA: H2O: Formic Acid (2:7:0.5:0.5V/V), and the chromatographic separation was performed on aluminum-backed silica gel 60 F254 plates. Ciprofloxacin was detected using UV light at 278nm. In factor screening studies, a 3-factor 17-run standard 3-level factorial design was used, and a Box-Behnken design was used to optimize HPTLC experimental parameters for obtaining anticipated chromatographic conditions. The basic method parameters were tested to understand risk assessment. Three independent parameters, such as saturation time, band duration, and migration distance, were chosen and analyzed based on the risk assessment to see if these three parameters influenced the responses. For ciprofloxacin, the method produces a compact and well-resolved band at Rf = 0.40 0.02. In the linear regression analysis performed on ciprofloxacin, the regression coefficient was found to be r2 = 0.996. Results: According to the International Council on Harmonization (ICH) guidelines, it was validated for validation parameters such as accuracy, precision, robustness, the limit of detection, and the limit of quantification. The proposed method for ciprofloxacin determination was found to be straightforward, precise, reliable, stable, and sensitive. Conclusion: The QbD method produced a more robust method that can generate accurate, high-quality, and reliable data during the process, and it can be effectively used in the routine inspection of Ciprofloxacin in the tablets dosage form.